2022
DOI: 10.1038/s41598-022-26399-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and anti-biofilm activity of Polygonum chinense L.aqueous extract against Staphylococcus aureus

Abstract: Polygonum chinense Linn. (Polygonum chinense L.) is one of the main raw materials of Chinese patent medicines such as Guangdong herbal tea. The increasing antibiotic resistance of S. aureus and the biofilm poses a serious health threat to humans, and there is an urgent need to provide new antimicrobial agents. As a traditional Chinese medicine, the antibacterial effect of Polygonum chinense L. has been reported, but the antibacterial mechanism of Polygonum chinense L.aqueous extract and its effect on biofilm h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…3 ). This finding was consistent with prior findings for Polygonum Chinese L. aqueous extract therapy of S. aureus [ 41 ]. It should be noted that the integrity of the bacterial cell surface is critical not only for cell protection but also for housing enzymes involved in cellular functions like the production of energy.…”
Section: Discussionsupporting
confidence: 93%
“…3 ). This finding was consistent with prior findings for Polygonum Chinese L. aqueous extract therapy of S. aureus [ 41 ]. It should be noted that the integrity of the bacterial cell surface is critical not only for cell protection but also for housing enzymes involved in cellular functions like the production of energy.…”
Section: Discussionsupporting
confidence: 93%
“…There have been many reports on the use of TEM for virus observation. For instance, cucumber mosaic virus, tobacco rattle virus, ranunculus mild mosaic virus, zucchini tigre mosaic virus, and staphylococcus aureus were observed in different host [23][24][25][26][27][28]. In this study, the Sphular virus particles were observed under TEM by negative staining for the samples and the diameter ranged from 80 to 120nm.…”
Section: Discussionmentioning
confidence: 60%
“…A few Polygonum species are traditionally used as Chinese medical herbs and possess antioxidant properties [37] . Additionally, P. chinense and other Polygonum extracts, such as Polygonum persicaria and Polygonum plejebum have been reported to contain antibacterial and antifungal properties [38] , [39] , [40] , [41] . The current study aimed to determine the efficiency of P. chinense extract as a dietary supplement on survival, haemato-biochemical and immune parameters following V. harveyi challenge.…”
Section: Introductionmentioning
confidence: 99%